2021
DOI: 10.1016/j.isci.2021.103205
|View full text |Cite
|
Sign up to set email alerts
|

Limited TCR repertoire and ENTPD1 dysregulation mark late-stage COVID-19

Abstract: T-cell exhaustion and dysfunction are hallmarks of severe COVID-19. To gain insights into the pathways underlying these alterations, we performed a comprehensive transcriptome analysis of peripheral-blood-mononuclear-cells (PBMCs), spleen, lung, kidney, liver and heart obtained at autopsy from COVID-19 patients and matched controls, using the nCounter-CAR-T-Characterization panel. We found substantial gene alterations in COVID-19-impacted organs, especially the lung where altered TCR repertoires are noted. Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
2
8
1
Order By: Relevance
“…These data indicate a failure in the immunosuppressive axis of adenosine generation by Treg cells during SARS‐CoV‐2 infection. Contrary to us, an upregulation in ENTPD1 (CD39) gene expression within the Treg pathway in peripheral tissues of severe COVID‐19 patients was previously reported, suggesting higher Treg suppression mediated by the CD39 axis may occur in the infected tissues during acute SARS‐CoV‐2 infection that may contribute to secondary infections by others pathogens (Wang, Veurich, Kalbasi, Shaefi, et al, 2021 ). On the other hand, Meckiff et al ( 2020 ) described an imbalance of Tregs cells and cytotoxic reactive CD4 + T cells in severe COVID‐19.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…These data indicate a failure in the immunosuppressive axis of adenosine generation by Treg cells during SARS‐CoV‐2 infection. Contrary to us, an upregulation in ENTPD1 (CD39) gene expression within the Treg pathway in peripheral tissues of severe COVID‐19 patients was previously reported, suggesting higher Treg suppression mediated by the CD39 axis may occur in the infected tissues during acute SARS‐CoV‐2 infection that may contribute to secondary infections by others pathogens (Wang, Veurich, Kalbasi, Shaefi, et al, 2021 ). On the other hand, Meckiff et al ( 2020 ) described an imbalance of Tregs cells and cytotoxic reactive CD4 + T cells in severe COVID‐19.…”
Section: Discussioncontrasting
confidence: 73%
“…In COVID‐19 patients, higher CD39 + T‐cell frequency was previously associated with the expression of PD‐1, confirming the hypotheses that SARS‐CoV‐2 infection induces a hyperactivated exhausted lymphocyte profile (Mathew, Giles, Baxter, Greenplate, et al, 2020 ), contributing to the T‐cell dysfunction in COVID‐19. Interestingly, Wang, Veurich, Kalbasi, Graham, et al ( 2021 ) identified increased CD39 expression in the lung, liver, spleen, and PBMCs from severe COVID‐19 patients, which correlated with days in the hospital, days in intensive care unit (ICU), and markers of coagulation, indicating associations between ectonucleotidases and disease progression. Similarly, CD39 messenger RNA (mRNA) as upregulated in peripheral blood leukocytes in association with higher soluble CD39 levels in severe COVID‐19 patients, which were related to the length of hospital day and ICU admission (Díaz‐García et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, those two epitopes have their slopes S the closest to 0 among all epitopes (Supplemental (ii) a general lymphopenia (11)(12)(13)(14)(15)(16); and (iii) a broad (not SARS-CoV-2-specific T cell exhaustion and/or impaired function (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). This was reported for immune cells both in the peripheral compartment (PBMCs) and in the lung and brain of symptomatic patients (13,69). The association of T cell exhaustion with COVID-19 severity is under debate with one study reporting no clear significant correlation with disease severity (70) (using a small number of patients) while two other reports, also using a small cohort of patients, discounted the link between higher expression exhaustion markers and impaired function of SARS-CoV-2specific CD4 + and CD8 + T cells in convalescent patients (71,72).…”
Section: Compared With Asymptomatic Covid-19 Patients Severely Ill Sy...mentioning
confidence: 72%
“…Therefore, single-cell data analyses that are performed differently at the single-cell level compared with the cell population level can provide a clinical added value. This method can effectively identify transcriptomic differences that reflect immunosuppression and low-grade inflammation trajectories between patients with bacterial versus viral sepsis [ 32 , 33 , 34 ], with specific consideration given to the level of expression of cytotoxic genes in those critically ill, severe manifestations and the overexpression of genes [ 35 ] involved during sepsis that cause the efficient clearance of invading pathogens. These patient cohort differences at the single-cell level can guide the use of immunomodulatory therapy [ 36 ], addressing both the scale of severity and the progression of disease by displaying specific functional diversity and the downregulation of effector functions [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%